Descriptions of seven new Acrogonia species from South America (Hemiptera: Cicadellidae: Cicadellinae: Proconiini) - Da Silva, Roberta Dos Santos; Cavichioli, Rodney R.; Takiya, Daniela M.; Mejdalani, Gabriel (Zootaxa, 2018)
Seven new species of the economically important sharpshooter genus Acrogonia Stål are described and illustrated: A. falcata sp. nov. (French Guiana and state of Amazonas, Brazil), A. felixi sp. nov. (department of Loreto, Peru), A. quintasi sp. nov. (state of Pará, Brazil), A. distincta sp. nov. (state of Amazonas, Brazil), A. dentata sp. nov. (department of San Martin in Peru, French Guiana, and states of Amazonas, Mato Grosso, Pará, and Rondônia in Brazil), A. luizi sp. nov. (province of Pastaza in Ecuador and state of Amazonas in Brazil), and A. lobulata sp. nov. (province of Orellana, Ecuador). In addition to the external morphology, color pattern, and male genitalia, detailed descriptions and illustrations of the female genitalia are provided for three of the new species (A. dentata, A. luizi, and A. lobulata). Females of the other four new species are unknown. Acrogonia includes now 39 species, being among the most species-rich genera of the Proconiini.